Exploring the Visual and Performative Appropriation of Shakespeare in Pakistani Theatres - Resshid, Zakia (Multicultural Shakespeare: Translation, Appropriation and Performance, 2024)
This research paper examines the experimental nature of appropriation focusing on The National Academy of Performing Arts (NAPA) renditions of Shakespeare’s Hamlet (1603) and Richard III (1597). It investigates how these adaptations bring about changes in both dramatic structure and artistic expression, dissecting visual and performative elements to uncover diverse meanings within live performances. The research delves into how NAPA’s creative choices offer new ways to examine Shakespeare’s universal themes—jealousy, incest, ambition, and hatred— through unconventional theatrical presentations, viewed from a post-dramatic perspective. Using Hans Thies Lehmann’s Post-dramatic theory (1960), it analyses alterations dramaturgical and aesthetical presentation such as plot construction, sign and symbol presentations. By bridging the gap between the art world and stagecraft, this study aims to deepen our understanding of how appropriation, aesthetics, and performance intersect. It also explores how these adaptations contribute to the global presentation of Shakespearean plays, offering insights from Pakistan’s theatrical landscape.